Kompetensi Pendamping Simantri dalam Pembuatan Biourine pada Kelompok Simantri di Kabupaten Tabanan - I MADE PRADNYA ANDITA; I GEDE SETIAWAN ADI PUTRA; I G A A LIES ANGGRENI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Competency Of Simantri Companion In Making Biourine In The Simantri Group InTabanan Regency. Integrated farming system (Simantri) is one of the superior programs of the Bali ProvincialGovernment to increase the role of the agricultural sector and support the making oforganic fertilizer. Organic fertilizers are in solid and liquid forms. extension agents play animportant role in increasing the competency of farmers in making liquid organic fertilizer.On the other hand, the competence of the instructor must also be adequate and understandin making liquid organic fertilizer. The purpose of this study was to determine thecompetency of Simantri's companion in biourine technology transfer and dissemination ofbiourine technology in the Simantri group in Tabanan Regency. The sample used in thestudy amounted to 30 respondents Data obtained in this study were processed and tabulatedusing quantitative analysis methods.Based on the results of research on simantri companioncompetencies in Tabanan Regency, it consists of (1) Mastery of biourine technology showsthat the category is very high, this is supported by giving information, reaching a score of 133 which shows very high categories in the parameters of management. (2) Competenciesobtained from the application process obtained in using the tools directly that reach a veryhigh category with a total score of 120 in the usage time parameter. (3) Then thecompetency in disseminating biourine technology which reaches a very high category isobtained on the indicator. counseling with a score of 131 in the percentage parameters.Thefacilitator gave more training to the Simantri group, especially in mastering technology, theapplication process and also dissemination in the making of biourine, and it was hoped thatthe Simantri companion would give more information about biourine so that the mastery ofmaking biourine was better.